A RARE DISEASE IN DIFFERANTIAL DIAGNOSIS OF DIFFUSE PAIN AND FATIGUE: WALDENSTROM MAKROGLOBULINEMIA - Zafer Günendi; Gülçin Kaymak Karataş; Vesile Sepici (Archives of Rheumatology, 2005)
Waldenström makroglobulinemia is a B cell neoplasm commonly seen in adults between 6th and 7th decade. The incidence of Waldenström makroglobulinemia is as low as 2,5/ million/ year and constitutes %2 of hematologic malignancies. It presents with constitutional symptoms such as pain, fatigue and weight loss. Here, a case presenting with diffuse pain, fatigue and high sedimentation rate diagnosed Waldenström makroglobulinemia after excluding other diseases is reported.